Family Approach and Spirituality to Support Drug Abuser Recovery - Ali Napiah Nasution; Ermi Girsang; Imelda Lingga; Frans Judea Samosir (Postgraduate, University of Mataram, 2023)
Indonesia is in a state of drug emergency, characterized by a high level of vulnerability and related crimes. Moreover, victims of drug abuse required assistance to recover from their substance abuse issues. Objective: The aim of this study was to analyze the influence of a family approach and spiritual experiences on the recovery process of individuals addicted to drugs in recovery centers in Medan. This research adopted a quantitative approach with cross-sectional design. A sample of 120 drug abusers was recruited using purposive sampling technique. Data was collected through questionnaires consisting of 20 items on the family approach, 20 items on spiritual experiences, and 32 items on drug use issues. Multiple linear regression analysis was conducted to examine the data. The findings revealed a significant influence of the family approach (p=0.024) and spirituality (p=0.000) on the improvement of the recovery process of individuals addicted to drugs undergoing recovery in Medan recovery centers. Most of them (55%) are in the state of contemplation. It is expected that the government maintain synergy and support the management of drug recovery centers, as well as social workers who have concern about drug abuse, along with families and the broader community, in order to effectively address this issue.Â